PERSONNEL POLICY AS A FACTOR OF COMPETITIVENESS OF THE ENTERPRISE - O. Dzhavadova; D. Shepelev; H. Galipov (Вестник Северо-Кавказского федерального университета, 2022)
In this article the problem of adaptation ofpersonnel policy of the enterprise to modern requirements of the market environment is considered. The authors analyze the ongoing changes associated with the irreversibility of economic reforms. Authors state that the movement towards healthy competition, forces enterprises to pay considerable attention to the long-term aspects of personnel policy. The analysis made it possible to draw a conclusion about the importance of competent selection, placement and use ofpersonnel as a necessary condition for improving the stability of the enterprise in a competitive environment